Flight to Safety in Deindustrialized Cities: Perceptions of School Safety in Charter and Public Schools in Detroit, Michigan. Issue 3 (March 2020) - Hamlin, Daniel
Safety is one of the primary reasons why parents report seeking out a school of choice in depressed cities with a high proportion of charter schools. However, little empirical research has examined how parents assess school safety in these settings. This study explores factors that parents associate with school safety in Detroit, Michigan by conducting semi-structured interviews with parents ( n = 31) in both charter and public schools. To contextualize parents' perceptions of school safety, teachers ( n = 23) were also interviewed. Findings indicate that parental perceptions of safety were shaped by school building conditions, school disciplinary environment, school-based parental involvement, student selection, and school location. These perceived indicators of safety suggest that components of school climate may be important for raising perceptions of safety in challenging contexts where school safety is a pressing concern.